Information processing apparatus and information processing method - XULE QIU; HIROSHI OKAMOTO (2018)
Information processing apparatus and information processing method. The information processing apparatus comprises: a unit obtaining input data that represents attributes of each subject among subjects; a generating unit generating a bipartite network which includes the subjects and the attributes included in the input data as nodes and in which a node that corresponds to each subject among the subjects are connected to nodes that correspond to the attributes of the subject via links; and a clustering unit performing clustering of a group of the nodes by performing iterative calculations of astochastic process of transitions between the nodes via the links in the bipartite network. 信息处理设备和信息处理方法。种信息处理设备包括：获取表示对象中的每个对象的属性的输入数据的单元；生成单元，所述生成单元生成二分网络，所述二分网络包括作为节点包括在所述输入数据中的对象和属性，并且在所述二分网络中，与所述对象中的每个对象对应的节点经由链路连接到与所述对象的属性对应的节点；以及聚类单元，所述聚类单元通过执行在所述二分网络中经由链路在所述节点之间的转移的随机过程的迭代计算，来执行所述节点的组的聚类。